Surnames, geographic altitude, and digital dermatoglyphics in a male population from the province of Jujuy (Argentina) - Dipierri, Jose Edgardo (2014)
The possible association between finger dermatoglyphic patterns and altitude and surname distribution was analyzed in a sample of adult males from the province of Jujuy, Argentina. We also investigated the biological affinity of this population with other South American natives and admixed populations. Fingerprints were obtained from 996 healthy men, aged 18–20 years, from the highlands (HL: 2500 m, Puna and Quebrada) and lowlands (LL: Valle and Selvas). Surnames were classified into native/autochthonous (A) or foreign (F), resulting in three surname classes: FF, when both paternal and maternal surnames were of foreign origin; FA, when one surname was foreign and the other was native; and AA, when both surnames were native. Frequencies of finger dermatoglyphic patterns – arches (A), radial loops (RL), ulnar loops (UL), and whorls (W) – were determined for each digit in relation to geographic location, altitude, and surname origin, resulting in the following categories: HL-FF, HL-FA, HL-AA, LL-FF, LL-FA, and LL-AA. The statistical analyses showed that UL and RL were more common in individuals of HL origin, whereas W and A were more frequent in the LL males (p < 0.05). Significant associations were observed between finger dermatoglyphic patterns and surname origin when geographic altitude was considered. In the HL group, UL was associated with AA and FA; in the LL group, the presence of A was associated with FF and FA. The distribution of dermatoglyphic patterns shows that the population of Jujuy belongs to the Andean gene pool and that it has undergone differential levels of admixture related to altitude.